Analisis Fungsi Dasar Manajemen dalam Pengelolaan Madrasah Tsanawiyah Negeri - Syifa Delfiani Gunawan; Mulyawan Safwandy Nugraha (Institut Agama Islam Hidayatullah Batam, 2025)
This study analyzes the application of basic Islamic education management functions at MTsN 2 Bandung using a descriptive qualitative approach. The findings show that planning, organizing, implementing, and controlling are carried out systematically and integrated with the values of amanah, shura, and ihsan. Managerial effectiveness is reflected in exemplary leadership, open communication, and teacher motivation. The study implies that integrating Islamic values strengthens organizational culture and service quality, and offers a more humanistic and effective governance model for madrasah management.